Everybody Can Dance—Except Aging Professional Dancers! A Discussion of the Construction of the Aging Dancing Body in Four Dance Texts - Rustad, Hilde; Engelsrud, Gunn Helene (Frontiers in Sports and Active Living, 2022)
The subject of the article is a critical investigation of research concerning age and dance. Our objective is to investigate whether and how researchers express their ideas about dance and age in a selection of research papers. We are particularly interested in whether researchers are reproducing an instrumental understanding of age in the context of dance and whether discourses of dance define bodies as older or younger in ways that differ from the definitions used in other social contexts. What kind of assumptions about the abilities of dancers form the baseline expectations of researchers? We wonder if harming the body is an implicit part of dance practice that operates as a tacit premise in the understanding of age and dance. Through a document analysis of several research texts on dance and age, we try to identify what kinds of meanings, expectations, and bodies such documents convey and produce. One of our findings from the analysis of the literature is that young dancers from western European countries and the U.S. are concerned with age throughout their entire career, while in dance practices in Japan, being an older dancer is regarded as a as a value that gives flavor and energy to both to aging and dance in a shared interaffective and mutual space.